Standards, Procedures and Indicators in the Functioning of Social Services for the Elderly - Sorina Corman (Research Developments in Arts and Social Studies Vol. 3, 2022)
The paper presents an example of measuring the quality of social services for the elderly and an analysis of the concept of the elderly as reflected in the quality management documents of the social work system. The classic steps of content analysis were followed in the analysis process: inventory of standards, indicators, procedures and tools; standardization of the information contained in the aforementioned quality standards, classification into units of analysis, establishment of the main categories of analysis, coding and final analysis of the data. Three categories of information emerged from the analysis: senior citizens in specific roles, the elderly in the relational system and the elderly in the dynamics of integration. The main conclusion of the paper highlighted the importance of developing intervention techniques and tools for social workers in conjunction with the dimensions resulting from the analysis of the quality management system.